Is human chorionic gonadotropin supplementation beneficial for frozen and thawed embryo transfer in estrogen/progesterone replacement cycles?: A randomized clinical trial. (4th April 2017) - Shiotani, Masahide; Matsumoto, Yukiko; Okamoto, Eri; Yamada, Satoshi; Mizusawa, Yuri; Furuhashi, Kohyu; Ogata, Hiromi; Ogata, Seiji; Kokeguchi, Shoji
Abstract: Aim: Human chorionic gonadotropin (hCG) is used frequently for luteal support in fresh in vitro fertilization cycles as it induces progesterone secretion from the ovaries after oocyte retrieval and modulates the endometrium for implantation in fresh cycles. In contrast, hCG is not usually used for the transfer of cryopreserved‐thawed embryos in estrogen/progesterone replacement cycles because ovulation is suppressed. However, several studies have shown that luteinizing hormone and hCG receptors are present in the human endometrium and that hCG can directly induce the decidualization of endometrial stromal cells in vitro. Thus, this study evaluated whether hCG supplementation can be beneficial for cryopreserved‐thawed embryo transfer in estrogen/progesterone replacement cycles. Methods: One‐hundred‐and seventy‐three cryopreserved‐thawed embryo transfer cycles with estrogen/progesterone replacement were divided randomly into two groups. Transdermal oestradiol was used in combination with vaginal progesterone suppositories for HR. The embryo transfer was performed on day 17 and/or day 20 of the HR therapy cycle in both groups. In Group A, 3000 IU of hCG was administered on days 17, 20, and 23. In Group B, hCG was not used. Results: There was no significant difference in the average age of the patients, the average number of previous assisted reproductive technology cycles, or the average number of embryo transfers between the two groups. The rates of pregnancy and implantation per embryo were 37.2% and 25.3%, respectively, in Group A and 35.6% and 21.7%, respectively, in Group B. The pregnancy and implantation rates were similar in both groups. Conclusion: Supplementation with hCG is not beneficial for cryopreserved‐thawed embryo transfer in estrogen/progesterone replacement cycles.